HOMA estimated insulin resistance as a marker for angiographic severity of coronary artery disease in non-diabetic and non-obese patients - Mohamed Eid; Sherif A. Sayed; Nayel A. Zaki; Amera M. F. Hamdy; Ali M. A. Altaher (Babol University of Medical Sciences, 2023)
Background: Insulin resistance (IR) examined by homeostasis model assessment of insulin resistance (HOMA-IR) measures increased carotid atherosclerosis risks in non-diabetic and non-obese persons. The information about the relationship between IR and coronary atherosclerosis severity among non-diabetic and non- obese population showed conflicting results. The goal of the current study was to assess the relationship that links IR and coronary artery disease (CAD) among non-diabetic and non-obese Egyptian populations. Methods: 112 non-diabetic and non-obese patients were included in this study. These patients underwent coronary angiogram (CA) either due to acute coronary syndrome (ACS) or chronic stable angina with positive exercise tests. Results: Our study found a strong association between HOMA-IR and Gensini score (r = 0.831, with p<0.001) in general population. The HOMA-IR was the most influential independent predictor for the presence of extensive coronary atherosclerosis. Non-diabetic and non-obese people carrying the risk of developing the three-vessel disease (3VD) may be identified with a HOMA-IR score of over 5.9 according to the ROC curve analysis with a sensitivity of 67.7%. Conclusion: IR that developes in non-diabetic non-obese individuals coincides with more severe and more outspread CAD. In non-diabetic non-obese populations who need a CA, a single HOMA-IR value is higher than 5.9 may imply an elevated risk for clinically significant CAD. As insulin resistance is a reversible process, risk stratifications of CAD in non-diabetic non-obese populations could include HOMA-IR as one of its parameters.